Cannabinoids, cannabis, and cannabis-based medicine for pain management: a protocol for an overview of systematic reviews and a systematic review of randomised controlled trials. (May 2019) - Fisher, Emma; Eccleston, Christopher; Degenhardt, Louisa; Finn, David P.; Finnerup, Nanna B.; Gilron, Ian; Haroutounian, Simon; Krane, Elliot; Rice, Andrew S.C.; Rowbotham, Michael; Wallace, Mark; Moore, R. Andrew
Abstract : Abstract: Pain is an experience that affects many people worldwide and is associated with higher mortality and lower quality of life. Cannabinoid, cannabis, and cannabis-based medicines (CBMs) are thought to reduce pain, but a proliferation of different products has led to variability in trials, creating a challenge when determining the assessment of efficacy in systematic reviews. We will conduct 2 systematic reviews commissioned by the International Association for the Study of Pain Task Force on the use of cannabinoids, cannabis, and CBMs for pain management: first, an overview review of systematic reviews to summarise the evidence base and second, a systematic review of randomised controlled trials of cannabinoids, cannabis, and CBMs. In these reviews we will determine the harm and benefit of CBM from the current literature and will interpret the findings in light of the quality of evidence and reviews included. We will search online databases and registries in any language for systematic reviews and randomised controlled trials. We will include studies that evaluate any cannabinoid or CBM vs any control for people with acute and chronic pain. Our primary outcomes for both reviews are the number of participants achieving (1) a 30% and (2) 50% reduction in pain intensity, (3) moderate improvement, and (4) substantial improvement. A number of secondary outcome measures will also be included. We will assess risk of bias and quality of evidence. We will analyse data using fixed and random effect models, with separate comparators for cannabis and CBMs. Prospero ID (CRD42019124710; CRD42019124714). Abstract : Supplemental Digital Content is Available in the Text.